A Systematic Literature Review on Adolescent Moral Decadence in the Digital Era: Phenomena and Islamic Therapy Strategies - Arif Syofyan Hadi; Rahmad Hakim; Dina Mardiana (Systematic Literature Review Journal, 2026)
This Systematic Literature Review (SLR) research synthesizes findings from five scientific articles that focus on the vital role of Islamic Religious Education (PAI) in overcoming the crisis and moral decadence among the Young Generation triggered by the minimal internalization of positive values in education, the lack of family roles, and the challenges of the digital era. The results of the synthesis show that overcoming the moral crisis requires a comprehensive approach, including: first, Affective Approach: PAI must transform from a cognitive focus to an Affective Approach based on the core values of the Qur'an (Ihsan, Rahmah, Tawadhu', Sabr, Amanah) to touch students' spirituality; second, Social Integration: PAI must be integrated with social reality to foster social piety through community-based programs (mosques) that ground Islamic values contextually; and third, Digital Adaptation: PAI teachers play a strategic role as moral role models and are required to adapt to the digital era through strategies for utilizing interactive technology and forming positive digital communities to overcome the influence of negative social media content. Overall, PAI is a central pillar whose effectiveness depends on strong collaboration between educational environments and the ability of teachers to be technologically literate spiritual-affective guides.